Another patient has cured HIV infection - de Mendoza, Carmen; Soriano, Vicente (NLM (Medline), 2022)
Up to date, a sterilizing cure of HIV-1 infection has been reported in only two persons living with HIV-1 who underwent allogeneic hematopoietic stem cell transplantations from donors who were homozygous for the CCR5 Δ32 gene polymorphism. They are known as the “Berlin patient” (Hutter et al. N Engl J Med 2009) and the “London patient” (Gupta et al. Nature 2019), respectively.
Keywords: HIV infections; humans; Scopus; JCR